Pediatric NMOSD: A Review and Position Statement on Approach to Work-Up and Diagnosis - Tenembaum, Silvia; Yeh, E. Ann; , The Guthy-Jackson Foundation International Clinical Consortium (GJCF-ICC); Abboud, Hesham; Alroughani, Raed; Altintas, Ayse; Amezcua, Lilyana; Apiwattanakul, Metha; Asgari, Nasrin; Banwell, Brenda; Bennett, Jeffrey; Bichuetti, Denis; et al. (Frontiers in Pediatrics, 2020)
Neuromyelitis Optica Spectrum Disorder (NMOSD) is a chronic relapsing condition characterized by inflammatory episodes of the central nervous system, primarily affecting the optic nerves and spinal cord, but also involving other regions of the central nervous system including the area postrema, periaqueductal grey matter, and hypothalamus. Knowledge related to pediatric manifestations of NMOSD has grown in recent years, particularly in light of newer knowledge regarding the importance of not only antibodies to aquaporin 4 (AQP4 IgG) but also myelin oligodendrocyte glycoprotein (MOG IgG) in children manifesting clinically with this syndrome. In this review, we describe the current state of the knowledge related to clinical manifestations, diagnosis, and chronic therapies for children with NMOSD, with emphasis on literature that has been published in the last 5 years. Following the review, we propose recommendations for the assessment/follow up clinical care, and treatment of this population.